The Raman coupling coefficients of calcium and sodium silicate melts in high-frequency region - SiOT model study - Wu, Yong-Quan; Jiang, Guo-Chang; You, Jing-Lin; Chen, Hui; Xu, Kuang-Di (Journal of physics. Conference series, 2006)
The Raman coupling coefficient (CC), which was defined by Shuker and Gammon, of silicate melt in high-frequency region, is still an untouched subject but the key parameter for quantitatively processing the Raman spectra (RS) to achieve the abundance of microstructural units. In this paper, we present the results of a newly constructed model - SiOT model (Wu et al) about the Raman coupling coefficients of calcium and sodium silicate melts, especially in the high-frequency region. This new model combines classical MD simulation with decomposition of simulated configurations and vibrational analysis including Wilson's GF matrix method, electro-optical parameter method (EOPM) and bond polarizability model (BPM). The displacement dependence of the cluster polarizability through the combination of EOPM and BPM connotes the description of the frequency dependence of CC. This allows us to make a direct comparison for the first time between the calculated VDOS (vibrational density of states) and RS within the entire frequency range. A strong conclusion was given that the partial VDOS, RS and CC are all the intrinsic properties of respective Qi species, and the only variable inducing the change in total VDOS, RS and CC is the change of microstructure, i.e. the distribution of the Qi.